Influence of vibrational anharmonicity and vacancies on thermodynamic properties of the rare gas crystals - Karasevskii, A.I.; Holzapfel, W.B. (Физика низких температур, 2003)
A statistical method is used to calculate thermodynamic properties of Ar, Kr and Xe (isobaric and isochoric heat capacity, bulk modulus, thermal expansion coefficient, interatomic distances, Grüneisen parameter), and good agreement with experimental values is observed. It is shown that at high temperature, slightly above the melting point of the rare gas crystals, an instability of the crystalline state occurs. As temperature approaches this instability the isobaric heat capacity and the thermal expansion coefficient show strong increases similar to the experimentally observed anomalies.